Key Genes and Pathways Associated With Inner Ear Malformation in SOX10 p.R109W Mutation Pigs - Hao, Qing-Qing; Li, Liang; Chen, Wei; Jiang, Qing-Qing; Ji, Fei; Sun, Wei; Wei, Hong; Guo, Wei-Wei; Yang, Shi-Ming (Frontiers in Molecular Neuroscience, 2018)
SOX10 (SRY-box 10) mutation may lead to inner ear deformities. However, its molecular mechanisms on inner ear development are not clear. In this work. The inner ear morphology was investigated at different embryonic stages of the SOX10 mutation miniature porcine model with sensorineural hearing loss, and high-throughput RNA-seq and bioinformatics analyses were applied. Our results indicated that the SOX10 mutation in the miniature pigs led to an incomplete partition of the cochlea, a cystic apex caused by fusion from middle and apical turns, cochlear modiolar defects and a shortened cochlear duct. The model demonstrated 173 DEGs(differentially expressed genes) and 185 lncRNAs(differentially expressed long non-coding RNAs). The down-regulated DEGs most significantly enriched the inflammatory mediator regulation of the TRP channels, arachidonic acid metabolism, and the salivary secretion pathways, while the up-regulated DEGs most significantly enriched the systemic lupus erythematosus and alcoholism pathways. Based on gene cluster analysis, we selected four gene groups: WNT1, KCNQ4, STRC and PAX6.